Design Perancangan Forum Diskusi Karyawan Berbasis Web di PT. Rlogic - Achmat Mustajib; Sulistianto Sutrisno Wanda (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
When a company operates, demands and responsibilities are attached responsibility for the company concerned for the local community in surroundings. Communication in internal discussions can be said to be more important rather than external communication, because discussion must function effectively in achieve its goal of maintaining relations with all publics within the discussion. In a In the company there are many people from various social and different professionals working for the same goal. It is hoped that the Employee Discussion Online Forum can provide benefits and ease of discussion, efficient and reliable information services updates to mployees and makes it easier for employees to exchange various ideas and information and can also resolve conflicts internals. design The development of this Employee Discussion Online Forum via Internet by website uses PHP and MySQL applications.